Arenavirus phylogeny: a new insight - Albariño, César G. (1998)
Arenaviridae is a worldwide distributed family, of enveloped, single stranded, RNA viruses. The arenaviruses were divided in two major groups (Old World and New World), based on serological properties and genetic data, as well as the geographic distribution. In this study the phylogenetic relationship among the members of the Arenaviridae was examined, using the reported genomic sequences. The comparison of the aligned nucleotide sequences of the S RNA and the predicted amino acid sequences of the GPC and N proteins, together with the phylogenetic analysis, strongly suggest a possible kinship of Pichinde and Oliveros viruses, with the Old World arenavirus group. This analysis points at the evolutive relationships between the arenaviruses of the Americas and can be used to evaluate the different hypotheses about their origin.